Rediscovering Korean cinema - Lee, Sangjoon (University of Michigan Press, 2020)
South Korean cinema is a striking example of non-Western contemporary cinematic success. Thanks to the increasing numbers of moviegoers and domestic films produced, South Korea has become one of the world’s major film markets. In 2001, the South Korean film industry became the first in recent history to reclaim its domestic market from Hollywood and continues to maintain around a 50 percent market share today. High-quality South Korean films are increasingly entering global film markets and connecting with international audiences in commercial cinemas and art theatres, and at major international film festivals. Despite this growing recognition of the films themselves, Korean cinema’s rich heritage has not heretofore received significant scholarly attention in English-language publications.